A DEVELOPMENT OF AN EFFECTIVE METHOD FOR THE SYNTHESIS OF 2-(5-OXO-4,5-DIHYDRO-1,2,4-OXADIAZOL-3-YL)BENZOIC ACID: DOI: https://doi.org/10.17721/1728-2209.2020.1(57).13 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
2-(5-Oxo-4,5-dihydro-1,2,4-oxadiazol-3-yl)benzoic acid was synthesized using a new effective method – thermal heterocyclization of 3-(hydroxyimino)isoindolin-1-one, which occurs as a result of its interaction with 1,1'-carbonyldiimidazole (CDI) and subsequent base-promoted cycle-opening of the obtained intermediate 3H,5H-[1,2,4]oxadiazolo[3,4-a]isoindole-3,5-dione.  Direct cyclization of 3-(hydroxyimino)isoindolin-1-one by the reaction with diethyl carbonate in the presence of sodium ethylate in ethanol at room temperature and under heating was unsuccessful. The same result was observed when using triphosgene in the presence of triethylamine in dichloromethane. Treating 3-(hydroxyimino)isoindolin-1-one with methyl chloroformate gave 3-(((methoxycarbonyl)oxy)-imino)isoindolin-1-one which was thermally stable and was not cyclized into the desired acid by boiling in toluene and o-xylene for 24 hours.  The reflux of the excess of CDI with 3-(hydroxyimino)isoindolin-1-one in anhydrous ethyl acetate and subsequent alkaline hydrolysis gave the desired 2-(5-oxo-4,5-dihydro-1,2,4-oxadiazol-3-yl)benzoic acid in a total yield of 90%. An attempt to stop the process at the stage of formation of the intermediate 3H,5H-[1,2,4]oxadiazolo[3,4-a]isoindole-3,5-dione by carrying out the reaction in the absence of a base failed. Its partial hydrolysis took place during the reaction, and especially at the stage of isolation, and as a result a mixture of 3H,5H-[1,2,4]oxadiazolo[3,4-a]isoindole-3,5-dione and 2-(5-oxo-4,5-dihydro-1,2,4-oxadiazol-3-yl)benzoic acid was formed in a ratio of about 2:3. The obtained substance after mixing with aqueous-methanolic NaOH solution and subsequent acidification with 1M HCl was quantitatively converted into the pure desired acid. The developed method allows the use of 3-(hydroxyimino)isoindolin-1-ones as convenient starting materials for the preparation of vic-(5-oxo-4,5-dihydro-1,2,4-oxadiazol-3-yl)aromatic acids and subsequently related compounds, in particular isomeric vic-carbamimidoyl(hetero)aromatic carboxylic acids, which cannot be obtained by other currently known methods. All the compounds obtained during the development of the method were studied by means of NMR spectroscopy.
Keywords: 3-(hydroxyimino)isoindolin-1-ones, 2-(5-oxo-4,5-dihydro-1,2,4-oxadiazol-3-yl)benzoic acids, 3H,5H-[1,2,4]oxadiazolo[3,4-a]isoindole 3,5-dione, heterocyclization.